Social Exclusion and Ethical Responsibility: Solidarity With the Least Skilled - Schokkaert, Erik (Journal of business ethics, 1999)
Social integration is a basic ingredient of any description of a good society. We feel that all people should get the opportunity to realise their full human potential, i.e. to realise their own goals and aspirations. In this paper we claim that this is also part of the responsibility of private sector firms and, therefore, an integral aspect of business ethics. We first argue against the (popular) conviction that the situation of the unemployed is their own responsibility, either because they choose to be unemployed (section 2), or because they choose to be low skilled (section 3). As a consequence, we do not believe that the dismantling of the social security system or the restructuring of the educational system can fully solve the problem of the least skilled in our societies. Nor do we think that the integration of the least skilled is a matter for government policy alone. In section 4 we argue that job creation remains indispensable for a real attack on the problem of social exclusion. In section 5, we highlight the important role of the private sector in this regard. Such job creation will require a lot of effort and imagination at the micro-level of the firm and a lot of creative thinking about how to structure the macrosocial market environment within which private firms operate.